2007
DOI: 10.1016/j.heares.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Does cochlear implantation and electrical stimulation affect residual hair cells and spiral ganglion neurons?

Abstract: Increasing numbers of cochlear implant subjects have some level of residual hearing at the time of implantation. The present study examined whether (i) hair cells that have survived one pathological insult (aminoglycoside deafening), can survive and function following long-term cochlear implantation and electrical stimulation (ES); and (ii) chronic ES in these cochleae results in greater trophic support of spiral ganglion neurons (SGNs) compared with cochleae devoid of hair cells. Eight cats, with either parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 49 publications
(84 reference statements)
16
105
5
Order By: Relevance
“…Lousteau (1987), Hartshorn et al (1991), and Miller and Altschuler et al (1995; demonstrated increased SG cell survival after chronic ICES in guinea pigs deafened by ototoxic drugs and implanted as young adults. In contrast, other studies have failed to find trophic effects in vivo in guinea pigs , and Shepherd and coworkers (Araki et al, 1998;Shepherd et al, 1994) found no overall difference in SG cell survival after chronic ICES in cats deafened at an early age by ototoxic drugs, although recently they reported a significant regional increase in SG survival in partially deafened cats and a consistent increase in the size of stimulated SG cells (Coco et al, 2007).…”
Section: Factors Influencing Neurotrophic Effects Of Electrical Stimumentioning
confidence: 93%
“…Lousteau (1987), Hartshorn et al (1991), and Miller and Altschuler et al (1995; demonstrated increased SG cell survival after chronic ICES in guinea pigs deafened by ototoxic drugs and implanted as young adults. In contrast, other studies have failed to find trophic effects in vivo in guinea pigs , and Shepherd and coworkers (Araki et al, 1998;Shepherd et al, 1994) found no overall difference in SG cell survival after chronic ICES in cats deafened at an early age by ototoxic drugs, although recently they reported a significant regional increase in SG survival in partially deafened cats and a consistent increase in the size of stimulated SG cells (Coco et al, 2007).…”
Section: Factors Influencing Neurotrophic Effects Of Electrical Stimumentioning
confidence: 93%
“…However, since the stimulation was not continuous, the total duration of electrical stimulation was limited to a small fraction of the time that was spent in the testing booth. As a result, the subjects in this study received much less electrical stimulation as compared to other studies that employed chronic electrical stimulation to test safe limits or protective effects of electrical stimulation (Walsh et al 1981;Duckert and Miller 1982;Duckert 1983;Ni et al 1992;Xu et al 1997;Coco et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…One animal study suggests that cochlear implantation surgery causes hearing loss due to the direct acute trauma of electrode insertion combined with subsequent apoptotic cell death of hair cells (Eshraghi et al 2005). The effects of electrical stimulation on hair cells have also been studied in the past in several animal species, with mixed results that depend partly on charge density (Walsh et al 1981;Duckert and Miller 1982;Duckert 1983;Ni et al 1992;Xu et al 1997;Coco et al 2007). Thus, cochlear pathology may be a result of the implantation surgery or the electrical stimulation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, reduction in somatic size reflects reduced metabolic requirements of these neurons due to reduced spike activity after deafness (Hartmann et al 1984;Liberman and Kiang 1978;Shepherd and Javel 1997). When electrical stimulation from a CI is applied to reactivate these neurons, modest but significant increases in SG soma area in the stimulated cochleae have been reported (Araki et al 1998;Coco et al 2007;Leake et al 1999Leake et al , 2007. However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizementioning
confidence: 99%
“…In our laboratory, studies of cats deafened prior to hearing onset have shown that multichannel CI electrical stimulation applied over several months results in substantial improvement in SG neural survival (Leake et al 1999(Leake et al , 2007(Leake et al , 2008a above that seen in the contralateral deafened cochleae. Other studies, however, have not found evidence of trophic effects of electrical stimulation (Araki et al 1998;Coco et al 2007;Li et al 1999;Shepherd et al 1994). These disparities in findings suggest that differences among animal models, methods of stimulation (e.g., the position of stimulating electrodes, applied signals, and efficacy in exciting neurons across a broad sector of the spiral ganglion), and/or methods of analysis of SG density are critically important.…”
Section: Introductionmentioning
confidence: 99%